Sistem Kebijakan Pengelolaan Pendidikan Dasar - Ayu Kartika; Suryanti Eka Putri; Rahmat Firmansyah; Hafiz Hidayat (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
Basic education plays a central role in character building and preparing individuals for the future. To achieve optimal goals, the policy and management system of education (Pendas) must be analysed in depth. This study uses a qualitative method with a library study approach to evaluate the pros and cons of the Pendas policy system and Pendas management system. Content analysis of relevant literature revealed that the Pendas policy system provides clarity of national vision and educational inclusion, although it is prone to bureaucracy and slow in adaptation. On the other hand, the Pendas management system offers local adaptability and active participation, but may face inter-agency coordination challenges. This study provides in-depth insights into critical components such as curriculum policy, human resource management and education evaluation and highlights the need for integrative strategies to strengthen an inclusive and competitive education system.